INSTITUTIONAL FARMERS' LAND TO INCREASE FARMER'S PRODUCTION, PRODUCTIVITY AND INCOME - Titik Ekowati; Edy Prasetyo; Bambang Trisetyo Eddy (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
Farm land management institutional in term of consolidation and corporate farming programs are the management of farm land especially wet rice field to fulfill the optimum farm scale that manage by farmer’s group and to get the value for farmers. Research was aimed to develop the farmer’s institutional by land consolidation and corporate farming approach. Survey method was used for research. Dalangan Village, Tawangsari District and Dukuh Village, Mojolaban District were determined for research location by purposive method based on the farm institutional. Simple random sampling was used to get 40 respondents who joined the institutional program and 40 respondents who were not affiliated with land institutions. Data were analyzed by descriptively. The research was held by farmer’s empowerment and assistance at the farmers group to make use of innovation technology. Result of research showed that 28 ha wet rice field was integrated to the program of 4 farmer’s groups. The implementation of program answered the scarcity of land and labor and it can be easily to manage the production factors. The impact of the programs were increasing paddy production, prodoctivity, cost production effiecientcy by IDR 374.643,56/ha,/period increasing the usage of farm equipment, the created of the opportunity for employment, especially for women, to create the seedling and increasing the income of IDR 3.185.241.56/ha/period.